2013
DOI: 10.1039/c2cc37110c
|View full text |Cite
|
Sign up to set email alerts
|

Racemic marinopyrrole B by total synthesis

Abstract: The first synthesis of marinopyrrole B, which is highly active against methicillin-resistant Staphylococcus aureus, is described. The route involved constructing a pyrrole ring on the nitrogen of a 3-bromo-4,5-dichloropyrrole by N-alkylation with a special Michael acceptor having an allylic leaving group; the second pyrrole ring was then formed by a Paal-Knorr reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 25 publications
0
30
0
Order By: Relevance
“…64,65,69,70 The first, and thus far only, synthesis of marinopyrrole B (29) was reported in 2013 by Cheng et al (not shown), whereby the bipyrrole core in this case was instead generated through alkylation of a trihalogenated pyrrole, which underwent further manipulations to complete a Paal-Knorr construction of the second pyrrole ring, a precursor which allowed for the generation of rac-29. 71 Scheme 5: Convergent total synthesis of racemic marinopyrrole A (28).…”
Section: Marinopyrroles: Determination Of Enzymatically-imposed Atropmentioning
confidence: 99%
“…64,65,69,70 The first, and thus far only, synthesis of marinopyrrole B (29) was reported in 2013 by Cheng et al (not shown), whereby the bipyrrole core in this case was instead generated through alkylation of a trihalogenated pyrrole, which underwent further manipulations to complete a Paal-Knorr construction of the second pyrrole ring, a precursor which allowed for the generation of rac-29. 71 Scheme 5: Convergent total synthesis of racemic marinopyrrole A (28).…”
Section: Marinopyrroles: Determination Of Enzymatically-imposed Atropmentioning
confidence: 99%
“…Biosynthesis of marinopyrrole A via an N , C -bipyrrole homocoupling catalyzed by two flavin-dependent halogenases was reported by the Moore group [2], and racemic marinopyrrole B by total synthesis and a review of the marinopyrroles were reported by the Clive group [3,4]. After optimization of the key step to avoid the formation of an oxazepine byproduct [5] that was reported in our first total synthesis of marinopyrroles [8], we published the most potent symmetrical marinopyrrole derivative against MRSA and methicillin-resistant Staphylococcus epidermidis (MRSE) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their novel class of molecular structures and promising biological properties, marinopyrroles have attracted considerable attention [11,12,13,14,15,16,17,18,19]. We reported the first total synthesis of (±)-marinopyrrole A, along with 12 derivatives in early 2010 [12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Moore group published biosynthesis of marinopyrrole A via an N , C -bipyrrole homocoupling catalyzed by two flavin-dependent halogenases [17]. Most recently, racemic marinopyrrole B was reported by total synthesis from the Clive group [18]. During the preparation of this manuscript, a review of the marinopyrroles appeared [19].…”
Section: Introductionmentioning
confidence: 99%